Recent advances on TMDCs for medical diagnosis. (February 2021) - Meng, Si; Zhang, Yuyan; Wang, Huide; Wang, Lude; Kong, Tiantian; Zhang, Han; Meng, S.
Abstract: Transition metal dichalcogenides (TMDCs), such as MoS2 and WS2, have attracted much attention in biosensing and bioimaging due to its excellent stability, biocompatibility, high specific surface area, and wide varieties. In this review, we overviewed the application of TMDCs in biosensing and bioimaging. Firstly, the synthesis methods and surface functionalization methods of TMDCs were summarized. Secondly, according to the working mechanism, we classified and gave a detailed account of the latest research progress of TMDC-based biosensing for the detection of the enzyme, DNA, and other biological molecules. Then, we outlined the recent progress of applying TMDCs in bio-imaging, including fluorescence, X-ray computed tomographic, magnetic response imaging, photographic and multimodal imaging, respectively. Finally, we discussed the future challenges and development direction of the application of TMDCs in medical diagnosis. Also, we put forward our view on the opportunity of TMDCs in the big data of modern medical diagnosis. Graphical abstract: Transition metal dichalcogenides (TMDCs) have excellent performance in biosensing and bioimaging with different working mechanisms. This review summarizes the application of TMDCs in biosensing and bioimaging, and reflects the internal relationship between them. It helps inspire readers to use TMDCs as a platform to develop new diagnosis nano-composites with biosensing and bioimaging functions and form new diagnosis technologies. Image 1